Health-related quality of life of patients colonized or infected with multidrug-resistant organisms - Claus, Franziska; Ried, Walter (German Medical Science GMS Publishing House, 2017)
Aim: Due to their resistance against multiple antibiotics, multidrug-resistant bacteria (MDRO) impose higher costs upon health care providers and involve several risks for the health of patients. In the first place, the present paper aims to report on the applicability of a modified version of the German Short Form-36 (SF-36) Health Survey to address health-related quality of life (HRQoL) of inpatients colonized or infected with MDRO. Additionally, the study analyzes effects on HRQoL of affected patients.Methods: A prospective intervention study was conducted to implement a multimodal hygiene program against MDRO in acute care hospitals within the Health Region Baltic Sea Coast in Germany. HRQoL was assessed at discharge from the attending ward and six months after, respectively. In addition, the SF-6D as a preference-based measure of health was calculated. In order to control for confounders, statistical matching was performed using the variables age, gender, hospital, hospital status (i.e., intervention vs. control group of the empirical study) and attending ward as matching criteria. Results: Inpatients with MDRO (n=27) on average report lower scores for the majority of subscales. In addition, for these patients the component summary scores and the SF-6D are lower as well. With respect to follow-up examinations, the empirical data lead to no clear-cut impact on HRQoL for patients tested positive during their hospital stay.Conclusion: The modified version of the German SF-36 has been shown to be a suitable instrument to measure HRQoL of patients colonized or infected with MDRO. In particular, our results indicate that MDRO impose a risk upon the health of colonized patients. As a consequence, effective prevention measures against MDRO may not only be beneficial for health care providers but for affected patients and for society as well.